Implementasi Moora Pada Penilaian K3 Pemerintah Kota Tarakan - Romadan; Rusmin; Yusni Amaliah; Anto, Anto (STMIK PPKIA Tarakanita Rahmawati, 2019)
The Tarakan City Government, specifically the Organization Division of the Regional Secretariat (Setda), has struggled to maintain clean, organized, and aesthetically pleasing office environments, leading to numerous public complaints. These issues have negatively impacted the government's image and service quality. To address this, a decision support system is needed to help the Regional Secretary identify which government offices meet the standards for being comfortable and welcoming, based on Occupational Health and Safety (OHS) criteria outlined in Perwali No. 14 of 2017. Currently, Setda lacks an integrated information system to assess which offices meet these standards and identify which criteria require improvement. The existing evaluation method, done through Microsoft Excel, is inefficient, making the decision-making process less effective. In response, this study proposes a system that can categorize offices based on OHS standards and highlight criteria for improvement using the MOORA method. The study evaluates 16 government offices as alternatives, with data collected from interviews and the 2017 OHS evaluation sheets, covering eight criteria (seven benefit and one cost criterion) and 24 sub-criteria. The MOORA method is applied to generate final scores that provide rankings, categories, and improvement criteria. The OHS categories are defined as Green (scores between 70 and 90, indicating a high level of OHS), Yellow (scores between 50 and 70, indicating a moderate level of OHS), and Red (scores between 30 and 50, indicating a low level of OHS). The results show that the system is effective, informative, and efficient in displaying the OHS status of the offices. Out of the 16 offices, 11 are classified in the Green category, while 5 fall into the Yellow category. The Green category scores range from 70.78 to 79.63, and the Yellow category scores range from 66.26 to 69.09. The study identifies the need for improvements, particularly in Waste Management and Policies/Innovations by the Heads of Offices. This MOORA-based decision support system enables the government to better evaluate and improve the OHS performance of its offices, contributing to enhanced service quality and government reputation.